Floristic composition of two areas of Caatinga in Chapada do Araripe (Research, Society and Development, 2021)
The Caatinga is the main vegetation formation in northeastern Brazil, occupying most of its area and being of total importance to the region, it has many endemic species, but a small percentage of its extension is protected by environmental laws. It is in it that the Chapada do Araripe is inserted, present in the states of Piauí, Pernambuco and Ceará, which has an enormous plant diversity, has several phytophysiognomies such as: Cerrado, Cerradão, Carrasco, Humid Forest and Caatinga. The objective of this work was to describe the flora of two areas of Caatinga in Chapada do Araripe. Plant collections were carried out between September 2015 and May 2017. The material was pressed in the field, dehydrated and herborized. It was later sent to the Herbarium Caririense Dárdano de Andrade-Lima (HCDAL), of the Regional University of Cariri – URCA, for deposit and identification. 126 species belonging to 78 genera and 35 families were recorded. The most representative families in number of species were: Fabaceae (23 spp.); Malvaceae (15 spp.) and Euphorbiaceae (10 spp.) and the most representative genera were: Sida (10 spp.); Croton (9 spp.); Solanum (5 spp.) and Mimosa (4 spp.). The results obtained reveal a great diversity for the Chapada do Araripe, compared to other studies for the area. It can also be seen that Fabaceae and Euphorbiaceae are always in a prominent position in floristic studies for the Caatinga. The present study can significantly contribute to future conservation projects, providing data on the municipality's plant diversity.